Cytotoxic phenolic constituents from Hypericum japonicum. (August 2019) - Zhu, Wei; Qiu, Jie; Zeng, Yan-Rong; Yi, Ping; Lou, Hua-Yong; Jian, Jun-You; Zuo, Ming-Xing; Duan, Lian; Gu, Wei; Huang, Lie-Jun; Li, Yan-Mei; Yuan, Chun-Mao; et al.
Abstract: Nine undescribed compounds, including five xanthone derivatives, two flavonoids, one 2-pyrone derivative, and one undescribed naturally occurring compound, along with 30 known phenolic compounds, were isolated from Hypericum japonicum . In addition, hyperjaponols A and B were identified as racemates. The structures and absolute configurations of the undescribed compounds were determined by comprehensive MS, NMR spectroscopy, and electronic circular dichroism (ECD) calculations. The cytotoxic effects of the isolated compounds on two human tumour cell lines (HEL and MDA-MB-231) were evaluated by the MTT assay. Eighteen compounds showed good inhibitory activities against the HEL cell line, with IC50 values of 3.53–18.7 μM, while nine compounds exhibited moderate cytotoxicity against the MDA-MB-231 cancer cell line, with IC50 values ranging from 4.92 to 10.75 μM. Their preliminary structure-activity relationship of the isolated compounds was also discussed. Graphical abstract: Nine undescribed compounds and 30 known phenolic compounds were isolated from the whole plants of Hypericum japonicum . 19 compounds showed good inhibitory activities against the HEL and MDA-MB-231 cell lines with IC50 values of 3.53–18.7 μM. Image 1 Highlights: Nine undescribed compounds were isolated from Hypericum japonicum. Hyperjaponols A and B are racemates. 19 compounds showed good cytotoxic activities with IC50 values of 3.53–18.7 μM. The preliminary structure-activity relationship was also discussed.